Cyanide and fluoride colorimetric sensing by novel imidazo-anthraquinones functionalized with indole and carbazole - Batista, Rosa Maria Ferreira (2014)
Novel imidazo-anthraquinones functionalized with indole and carbazole have been synthesised and characterised and their evaluation as colorimetric chemosensors was carried out in acetonitrile as well as in acetonitrile/H2O (97:3) in the presence of several anions such as F-, Cl-, Br-, I-, CN-, NO3-, ClO4-, AcO-, BzO-, NO3-, ClO4-, HSO4- and H2PO4-. Additionally, their behaviour in the presence of H+ and OH- was also studied. Upon addition of CN- and F− to acetonitrile solutions of compounds 1-3, a marked colour change from yellow to orange was observed and the fluorescence emission of 1 and 2 was switched “on”. The recognition in organic aqueous solution lead to the selective and sensitive naked-eye detection (mM) of CN- for all receptors, with an easily detectable colour change from yellow to orange. The binding stoichiometry between the receptors and the anions was found to be 2:1. The binding process was also followed by 1H NMR titrations showing that two different binding modes occurred in the presence of fluoride or cyanide anions, which is in agreement with the spectrophotometric titrations.